Let's party! The impact of local festivities on the incumbent's electoral support. Issue 5 (3rd September 2021) - Guinjoan, Marc; Rodon, Toni
ABSTRACT: Do local festivities affect an incumbent's re-election prospects? Despite the relationship between local public policies and political behaviour is a central topic in political science, the effect of the organisation of leisure events on voting patterns has been largely neglected. Using data from Spain, we show that Mayors doubling the per capita amount of money devoted to local festivities during the last year of the legislature benefit by around two per cent points in upcoming elections. Two mechanisms account for this relationship. First, changes in the budget given over to festivities enhance the incumbent's support when the spending on local festivities during the previous years of the mandate was generous. Second, local festivities bring about positive rewards when the financial situation of the municipality is stable. Overall, our article sheds light on the need to consider other domains beyond "core" public policies when assessing the dynamics behind an incumbent's re-election.